Understanding the presence of military priests conducting military soul care in the Swedish armed forces: a medical sociological perspective - Grimell, Jan (Frontiers in Sociology, 2024)
In the 20th century, military medicine and psychiatry emerged as dominant paradigms in Western military contexts, shaping practices across recruitment, selection, training, screening, evaluation, diagnosis, and treatment. This approach paralleled trends in broader Western society, where it has faced criticism for medicalizing social, psychological, spiritual, and existential issues, often applying methods ill-suited to address certain forms of suffering. Despite this shift, alternative approaches embodied by military priests have maintained a meaningful role in the Swedish armed forces, in a country often, if somewhat misleadingly, regarded as one of the world’s most secularized. This article aims to elucidate the foundations, concepts, distinctiveness, and contributions of military soul care—militär själavård in Swedish—as practiced by military priests, or fältpräster, within the Swedish military context. Unlike chaplains (ordained and others) in other Swedish settings (e.g., hospitals, prisons, schools, airports, police) or military chaplains internationally, Swedish military priests operate within a unique mandate and purpose. Military soul care aims to build resilience to crises and wartime conditions, strengthening individuals’ will to defend and fight. The framework encompasses military soul care and counseling, advisory roles, education, ceremonies (including field sermons, prayers, memorials), and support for commanders in times of crisis. While military medicine and psychiatry continue to hold normative authority in a Swedish military society, there is a growing recognition that military personnel require more than physical conditioning to build mental resilience. Enduring the complex stresses of warfare demands approaches that transcend medical perspectives, addressing the human condition within a cultural and symbolic context. This article highlights key historical, societal, military, and ecclesiastical perspectives essential for understanding why this distinctive approach to military soul care has emerged in Sweden.